Plurality and Cultural Specificity of Service Design in East and Southeast Asia - Lee, Jung-Joo.; Baek, Joon Sang.; Yu, Eun.; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2025)
This open-access book expounds on how service design has been adopted and practiced in Asia, and how it has impacted especially the East and Southeast Asian countries. As service design is a socio-technical practice that is co-produced in context, the contributors focus on how service design has been applied and how it has evolved heterogeneously by interacting with the cultural and social dimensions of Asian countries. As the application domains of service design vary, this book covers adoptions and practices in different areas: Asian governments, the civic and grassroots sector, and business transformation. The contextual framing of the chapters is ultimately synthesized and analyzed in the concluding Discussion chapter of the book. This chapter takes into consideration the history and objects of service design, the interactions between research and practice, methodologies, and comparisons to practices in the Western World. This book appeals to students, researchers, and professionals in the field. .
Chapter 1 Introduction: Service Design in East and Southeast Asia as a Phenomenon -- Chapter 2 Design for Democratic Innovation in Taiwan -- Chapter 3 A Critical Review on the Citizen Participatory Design Group CPDG kukmintichaintan in South Korea Impacts and Limitations -- Chapter 4 Service Design in the Context of Pragmatic Governance: Cases of the Singapore Government -- Chapter 5 Innovation Shifts Moving towards a Sustainable System of Design Adoption in the Thai Government -- Chapter 6 Service Design for Innovating Hospitality Business in Japan -- Chapter 7 Adoption of Service Design in the Banking Industry A Focus on the Practice of Silent Designers -- Chapter 8 The Present and Future of Service Design in Hong Kong An Emerging Design Field -- Chapter 9 Four Levels of Service Design Interaction, Function, Organization, and Social Transition Cases of the Agrifood System in China -- Chapter 10 Service Design for ThaiHealth Food Program Exploring Participatory Policy Development -- Chapter 11 Design for Service with Robots in Elderly Care Facilities in Japan Focusing on HumantoHuman Interaction -- Chapter 12 Designing a Graduation Ceremony of Life A Reflection Journey Towards a Good Life in Old Age -- Chapter 12 Designing a Graduation Ceremony of Life A Reflection Journey Towards a Good Life in Old Age.
Keywords: Design; Industrial design; Industries; Design; Industrial Design; Industries